AFM study of microbial colonization and its deleterious effect on 304 stainless steel by Pseudomonas NCIMB 2021 and Desulfovibrio desulfuricans in simulated seawater - Yuan, S.J. (2014)
10.1016/j.corsci.2009.03.037